Fetal volvulus presenting with In utero bilious emesis: A case report - Felix Richter; Vanessa Eddy-Abrams; Harsha K. Garg; Peter S. Midulla; Veniamin Ratner (Elsevier, 2024)
Introduction: We report a case of fetal volvulus presenting with meconium-stained amniotic fluid, illustrating how meconium can mask in utero bilious emesis. Case presentation: The male neonate was born at 37 + 1 weeks gestation via c-section for maternal indications and admitted to the Neonatal Intensive Care Unit for respiratory distress presumably due to meconium aspiration. However, an initial x-ray was not consistent with meconium aspiration syndrome. Overnight, the orogastric tube drained 173 mL of dark green-tinged fluid and the bilirubin was elevated at 8.2 (threshold 7.4), prompting phototherapy. Orogastric feeds were attempted but unsuccessful. The orogastric output was originally attributed to swallowed meconium. However, the large volume, bilious color, persistent output, unexplained respiratory distress, and elevated bilirubin prompted an upper GI series (UGIS). The UGIS was consistent with a proximal obstruction that was likely present from birth. The patient underwent exploratory laparotomy which revealed a volvulus from malrotation that was repaired with detorsion and Ladd procedure. Despite a dusky bowel suggestive of ischemic changes, the bowel was fully pink after untwisting and no bowel needed to be resected. After untwisting, Ladd's bands were lysed, patency was demonstrated, and an appendectomy was performed. The baby was discharged on day-of-life 16 with full oral feeds and no complications. Conclusion: Persistent bilious gastric output in the setting of extensive meconium-stained amniotic fluid is an uncommon presenting sign of fetal volvulus from malrotation. Prompt recognition is important to prevent bowel necrosis.